(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This article analyzes the processes of religious and spiritual renewal that have taken place in Uzbek society during the period following the country’s independence. Particular attention is paid to the enhancement of religious freedom in the new era, the development of religious education, as well as the growth of religious culture and the processes of revival and renewal.